2016
DOI: 10.3389/fphar.2016.00361
|View full text |Cite|
|
Sign up to set email alerts
|

Preclinical and Clinical Assessment of Cannabinoids as Anti-Cancer Agents

Abstract: Cancer is the second leading cause of death in the United States with 1.7 million new cases estimated to be diagnosed in 2016. This disease remains a formidable clinical challenge and represents a substantial financial burden to the US health care system. Therefore, research and development of novel therapeutics for the treatment of cancer is of high priority. Cannabinoids and their derivatives have been utilized for their medicinal and therapeutic properties throughout history. Cannabinoid activity is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 111 publications
0
85
0
Order By: Relevance
“…CBR1, CBR2), and it is believed that signalling through this G-protein coupled receptor is required for CANN anticancer action. Most of the in vivo models of anticancer action of CANNs have focussed on cancers of the brain where there are high levels of CBR1, and a large proportion of these have indicated that CANN use is associated with decreased tumour growth and/or increased cell killing (6). These models have also shown the use of CANN can successfully support and enhance the action of other treatment modalities (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…CBR1, CBR2), and it is believed that signalling through this G-protein coupled receptor is required for CANN anticancer action. Most of the in vivo models of anticancer action of CANNs have focussed on cancers of the brain where there are high levels of CBR1, and a large proportion of these have indicated that CANN use is associated with decreased tumour growth and/or increased cell killing (6). These models have also shown the use of CANN can successfully support and enhance the action of other treatment modalities (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Current clinical studies mostly focus on patients with different types of glioblastoma, which are the most common and debilitating tumors of the CNS . These clinical results indicate that patients at least partially respond to cannabinoid treatments, and cellular and molecular examination of tissue samples indicates that the main reasons for the shrinkage of tumors appear to be the induction of autophagy and apoptosis and the decrease in vascularization of the tumor tissue . Though these studies are encouraging and further strengthen the potential use of cannabinoids in cancer therapy, further studies should be aimed at optimizing the use of cannabinoids in terms of patient selection based on genotyping or biomarker screening, or in combination with other anticancer agents such as recombinant DR ligands.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs can increase appetite, reduce pain, and reduce chemotherapy‐associated nausea and vomiting. Many in vitro and in vivo studies also indicate that cannabinoid drugs can reduce tumor volume and induce cancer cell death . Both the CB1 and CB2 receptors, their endogenous ligands, and regulatory proteins are expressed, functionally active, and generally up‐regulated in most tumor cell lines .…”
Section: The Cannabinoid System As a Target In Cancermentioning
confidence: 99%
See 2 more Smart Citations